Can Social Cognitive Theory Reduce Gender Inequality in Digitization among Women in Agricultural Activities in Tanzania? - John, Yuslida (Journal of cognition and culture, 2025)
This research examines the role of social cognitive theory in reducing gender inequality in the introduction of digitization among agriculturists’ women in Tanzania. This follows the low pace of digitalization adoption among women in the agriculture sector in Tanzania. The study experience from women farmers in two villages such as Membe and Chinangali in the Chamwino district in the Dodoma region with structural equation modeling indicates that social cognitive theory in terms of self-efficacy, observed learning, and observed behavior can influence digitization among agriculturalist women in Tanzania. While digitization has become inevitable in all sectors, with no exception to agriculture, understanding factors that motivate digitization among women farmers is critical given the low rate of adoption, despite the greater number of women involved in the sector.